The Development of Multiple Intelligences Theory (MIT) Based Fluent Reading Module for Slow Learners at Grade IV Inclusive Elementary School - Gaby Arnez; Ishartiwi Ishartiwi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This artilce aimed to investigate the practicality of Multiple Intelligences Theory (MIT) based module using the experimental indicators consisting of the module’s appearance, performance, the use of module, and the utilization of reading skills, to produce multiple intelligences theory based reading skill learning module assessed by the experts of media and learning materials, and to find out the effectiveness of multiple intelligences theory based reading skill learning module by improving word reading accuracy score. The researchers used ADDIE development model. All respondents are 300 students of SD Negeri Inklusi Tegalpanggung. The data collection technique used interview, questionnaire, and performance assessment. The data were analyzed by using descriptive-qualitative. The improvement of reading accuracy is examined through Normalized-Gain Test. The findings showed that multiple Intelligences theory based word recognition learning module which was used based on the examination with the category of “Very Good”. The products consist of introduction, content, and conclusion; the introduction consists of objectives, significances, and module map; the module consists of 16 learning materials divided into four sub-basic competencies and elaborated into four intelligences area; evaluation. Furthermore, the assessment from the expert 1 towards the learning module namely 3,7 with category “appropriate enough” and the expert II obtain mean value 4,01 classified into “appropriate” category and the media expert obtain mean value 4,47 with category of very appropriate. The effective learning module improves the reading skills assessed from the improvement of fluent reading skill with the post test score 92,6%. Keywords: Learning Module, Fluent Reading Skill, Multiple Intelligences Theory